Biodiesel Production From Sardine Flour Used Cooking Oil Using One Step Transesterification Techniques - Atmiral Ernes; Poppy Diana Sari; Rukmi Sari Hartati; I Nyoman Suprapta Winaya (Politeknik Pertanian Negeri Payakumbuh, 2019)
Diesel oil demand as energy source at industrial, transportation and electric generating sector are increasing and it resulted with the decreasing of fossil energy source backup. Biodiesel as an alternative energy source to substitute diesel oil can be utilized from used fried oil of sardine flour. The purpose of this research was to develop the technology to convert used fried oil of sardine flour to become biodiesel using one step trans-esterification technic as an alternative of renewable energy source and also to utilize waste of used oil. Biodiesel made using one step trans-esterification technic with NaOH catalyst concentration 0.5; 1.0; 1.5; 2.0 (% m/m) from total weight of oil and methanol. Trans-esterification process run for 30, 60 and 90 minutes at 65 temperature. The biodiesel obtained was analyzed using gas chromatography and mass spectrometer (GC-MS). The quality was determined by comparing its physicochemical properties and compared to the SNI standard 04-7182-2015. The result of GC-MS showed 10 peaks corresponding to ten methyl ester (biodiesel): octanoic acid methyl ester; decanoic acid methyl ester; dodecanoic methyl ester; tridecanoic acid, 12-methyl-, methyl ester; pentadecanoic acid methyl ester; hexadecatrienoic acid methyl ester, 9-hexadecenoic acid methyl ester, 9-hexadecenoic acid methyl ester, trans-13-octadecenoic acid methyl ester, hexadecanoic acid methyl ester. The biodiesel obtained has a density of 908 kg/m3, viscosity of 3.13 mm2/s, acid value of 0.29 mg-KOH/g found in treatment 1.5% NaOH and time process of 60 minutes. Viscosity and acid value were in a good agreement with SNI standard 04-7182-2015. The research shows that used fried oil of sardine flour has possibility as biodiesel source. Keywords: Biodiesel; sardine flour used cooking oil; trans-esterification